Beta-2 microglobulin predicts the outcome after autologous stem cell transplantation in non-Hodgkin lymphoma. Issue 1 (February 2015) - Atesoglu, Elif Birtas; Hacıhanefioglu, Abdullah; Gulbas, Zafer
Abstract: Autologous stem cell transplantation (ASCT) is an established therapeutic modality in the treatment of lymphomas, especially in the relapse setting. In the present study, we aimed to define pretransplantation factors including Beta-2 microglobulin (β2m) that influence outcomes following ASCT in patients with non-Hodgkin lymphoma (NHL). We analyzed retrospectively 78 NHL patients who had undergone ASCT from August 2010 to January 2013. The 2-year overall survival (OS) was 70% and the progression-free survival (PFS) was 60%. While remission status less than complete remission (CR) emerged to be a poor prognostic factor for OS in univariate analysis, high β2m levels and comorbidity indices revealed to be independent poor risk factors for both OS and PFS. The present study demonstrated that even if the patient is in CR before ASCT if he has high β2m, the 2-year OS decreases from 100% to 49%. Moreover, lymphopenia for the first time was demonstrated to predict PFS in ASCT in NHL patients. Our findings suggest that β2m at transplantation predict the outcome after ASCT in NHL and further investigation with larger sample sizes is warranted.